1982
DOI: 10.1677/joe.0.0940283
|View full text |Cite
|
Sign up to set email alerts
|

Priming effect of luteinizing hormone releasing hormone in the hypogonadal mouse

Abstract: We have investigated the LH response to LH releasing hormone (LH-RH) in female hypogonadal (hpg) mice in which the hypothalamus contains no LH-RH and the pituitary gland contains significantly less LH than in normal mice. Both the releasing action and the priming effect of LH-RH were not significantly different in hpg compared with normal mice. Raised plasma concentrations of oestradiol-17 beta reduced pituitary responsiveness to LH-RH in normal but not in hpg mice. These results show that in the mouse neither… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…LH radioimmunoassay The LH content of the pituitary homogenates and samples of media were estimated in duplicate by the ovine-ovine double-antibody radioimmunoassay of Niswender, Midgley, Monroe & Reichert (1968) as used previously in our studies of LH content and release from the mouse pituitary gland (e.g. Cattanach et al 1977;Fink et al 1982;Lewis et al 1985). Samples of pituitary homogenates and incubation media were assayed in duplicate aliquots of 20 and 50 pi respectively.…”
Section: Generalmentioning
confidence: 99%
See 1 more Smart Citation
“…LH radioimmunoassay The LH content of the pituitary homogenates and samples of media were estimated in duplicate by the ovine-ovine double-antibody radioimmunoassay of Niswender, Midgley, Monroe & Reichert (1968) as used previously in our studies of LH content and release from the mouse pituitary gland (e.g. Cattanach et al 1977;Fink et al 1982;Lewis et al 1985). Samples of pituitary homogenates and incubation media were assayed in duplicate aliquots of 20 and 50 pi respectively.…”
Section: Generalmentioning
confidence: 99%
“…The priming effect of LHRH, i.e. the capacity of the decapeptide to increase the responsiveness of pituitary gonadotrophs to itself (Aiyer, Chiappa & Fink, 1974), can be elicited in both normal and hpg mice (Fink, Sheward & Charlton, 1982;Lewis, Morris & Fink, 1984). This shows that neither long-term exposure to LHRH nor a normal pituitary content of luteinizing hormone (LH) is necessary for the releasing or priming action of LHRH.…”
mentioning
confidence: 99%
“…Studies employing injections of synthetic GnRH have previously shown that the hpg mice can respond to the hormone with a pituitary release of LH which is somewhat less than seen in normal animals (Iddon, Charlton & Fink, 1980), although the response to the priming action of GnRH on LH release was shown to be no different than normal (Fink, Sheward & Charlton, 1982). Multiple daily injections of GnRH for five days in hpg males significantly increased pituitary FSH content and testicular development (Charlton, Fink & Halpin, 1981), although seminal vesicle weights did not change during this brief period.…”
Section: Discussionmentioning
confidence: 98%
“…The magnitude of the priming effect of LHRH was determined according to the method of Fink et al [11], Animals were anesthe tized with urethane (1.2 g/kg body weight) administered intraperitoneally as a 10% solution in 0.9% NaCI (w/v) solution. About 20 min after urethane had been injected, an initial blood sample (0.2 ml) was withdrawn from the external jugular vein and 400 ng syn thetic LHRH (Peninsula Labs Inc., Belmont, Calif.) in 0.2 ml 0.9% NaCI were injected intravenously.…”
Section: Methodsmentioning
confidence: 99%